Modelando o ensino de balística por meio do pensamento computacional - Correa, Thomás Silva (2022)
This dissertation presents the results of a pedagogical intervention mediated by a didactic sequence aimed at teaching ballistics modeled by computational thinking. As a didactic resource, we used the free software PhET whose aim was to favor the concretion of Physics objects. The didactic sequence took into account educational problems obtained in loco. Such learning problems were determined after exploratory research, namely: mathematical difficulties, motivation/interest to learn Physics and the absence of practical classes. All the empirical research and the educational product application was carried out in times of the Covid-19 pandemic, through the remote teaching model. Anyway, as a product, we present a didactic sequence that is malleable, and can be transposed to any curricular subject inherent to Physics. However, even with this difficulty, after applying the product, there was an improvement in the students' performance in relation to the subject.